Risky Sexual Behaviours of Gender and Sexual Minorities - Yogi, Belpatra Nath (Journal of Health Promotion, 2019)
The article aims to explore the experiences on the risky sexual behaviours of the gender and sexual minorities in Surkhet district. It is a narrative study based on interview data. Thirty seven sexual minorities selected through snowball sampling were interviewed and the data were analyzed using thematic framework approach. The gender and sexual minority’s involve in sexual activity before their maturation at the age below 20. They have multiple sexual partners and have active sex life preferring anal and oral sexes the most. Many of them do not use condom in every sexual contact, do not visit health institutions for regular check-up, and do not test for HIV and other STDs which make them more vulnerable to diseases and poor health. They have made their sexual behaviors at more risk by their sexual involvement with drug users and their monetary involvement in sex. There is diversity in sexual orientations and behaviours among them. So an extensive and in-depth study in this issue is urgently required for the fuller understanding of socio-demographic influence on risky sexual behaviours of sexual minorities.